2011
DOI: 10.1093/bja/aer031
|View full text |Cite
|
Sign up to set email alerts
|

Consecutive, prospective case series of a new method for ultrasound-guided supraclavicular approach to the brachiocephalic vein in children

Abstract: This US-guided method offers a new possibility for central venous line placement in small children. It provides good needle guidance without any disturbing US shadow caused by bony structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
80
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 13 publications
4
80
0
4
Order By: Relevance
“…Although some operators have associated transverse imaging with an out-of-plane approach [40], this may not always be accurate because the internal jugular vein can be punctured in plane while being visualised in the transverse axis.…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some operators have associated transverse imaging with an out-of-plane approach [40], this may not always be accurate because the internal jugular vein can be punctured in plane while being visualised in the transverse axis.…”
Section: Recommendationsmentioning
confidence: 99%
“…Clinical examples include the internal jugular vein (Fig. 1), the external jugular vein, the innominate vein [40], the subclavian vein [18,41], the axillary/subclavian veins ( Fig. 2) and the cephalic vein.…”
Section: Recommendationsmentioning
confidence: 99%
“…The choice of side appears to reflect a personal preference. When placed at the patient side, the left SCV is the more accessible choice, as it allows the operator to hold the US probe in the left hand and the needle in the right hand more freely as stated by Breschan et al (8, 10). Still, when the operator is placed at the patient head, as Kulkani et al reported, the right SCV becomes the more logical choice for the same practical reasons (9).…”
Section: Right- Versus Left-sided Catheters As First Choicementioning
confidence: 99%
“…To date, 6 non comparative studies have been published in English literature. (8,9,11,12,20,21) First attempt success rate has been reported in 5 studies and has ranged from 65 to 82%. Overall success rate has ranged from 91% to 100%.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Finally left BCV may be a first choice compared to right BCV as it has shown improved success rate in previous study although we did not demonstrate statistically significant differences in first or overall success rates. (12) A C C E P T E D M A N U S C R I P T…”
Section: Accepted Manuscriptmentioning
confidence: 99%